Pigmented basal cell carcinoma: A rare clinical variant treated with excision and grafting - Manjunatha Puttaiah; Deekshith Rajmohan; Shishira R. Jartarkar (Our Dermatology Online, 2016)
Basal cell carcinoma (BCC) is a most common malignant tumour of skin. It develops on sun-exposed skin of lighter skinned individuals. It is a slow growing, locally invasive tumor. It is rare in dark skin because of the inherent photoprotection of melanin and melanosomal dispersion. The frequency of pigmented variant of BCC can reach up to 6% of total BCC in Hispanics. A 62yr old female came with the complaint of hyperpigmented plaque over the right lateral wall of the nose at the osseo-cartilagenous junction since 2yrs with evidence of central ulceration and bleeding. A wide local excision was planned with 5mm margins and covered with a full thickness graft obtained from the right retroauricular area. Post operation photographs taken. BCC is the most common non-melanoma skin cancer in the world. Though, pigmented BCC is the rare variant, it is becoming increasingly common in Asian population. UV radiation is the most important preventable risk factor for BCC. With increasing awareness and advent of newer treatment modalities, better cosmetic outcome with improved survival are expected.